2020
DOI: 10.2174/1573401315666191113154843
|View full text |Cite
|
Sign up to set email alerts
|

Post-harvest Attributes of Muskmelon (Cucumis melo): A Mini Review on the Potential of Value Addition

Abstract: Cucumis melo is a climacteric melon known for its peculiar musky aroma and sweet taste. It gained its popularity as thirst-quenching and refreshing fruit. Muskmelon is one of the commercially important fruit cultivated throughout the world in temperate, tropical and subtropical regions. The fruit shape may be round to oval, tan or straw coloured with netted peel. The flesh color may be white or orange. Muskmelon with yellow-orange coloured pulp with a network of intertwining green veins at the outside are high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Recent studies have demonstrated that these compounds play an important nutritional role. They are absorbed during digestion and play numerous regulatory roles in cellular metabolism [ 44 ]. Melon fruit contains polyphenols, a group of phytochemical compounds that have antioxidant, antimutagenic, antiproliferative, and antimicrobial capacities, and are involved in the prevention of and response to several pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that these compounds play an important nutritional role. They are absorbed during digestion and play numerous regulatory roles in cellular metabolism [ 44 ]. Melon fruit contains polyphenols, a group of phytochemical compounds that have antioxidant, antimutagenic, antiproliferative, and antimicrobial capacities, and are involved in the prevention of and response to several pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…agrestis having ovaries with short, appressed hairs. It is one of the best well-known fruits widely cultivated in humid, tropical and subtropical locations (39) and is greatly valued due to its unique taste, aroma, texture firmness and therapeutic advantages for health such as hematoma and hypertension mostly due to ascorbic acid, carotene, folic acid and potassium (40). Cantaloupe is ranked 4 th consumer acceptance in the list of the most preferred fresh fruits with impressive nutrients in the world market (41).…”
Section: Introductionmentioning
confidence: 99%
“…Melons contain calories, sodium and low in fat, source of potassium (K), vitamin C, vitamin B6, and vitamin A (Poverenov et al, 2014;Sultana & Rahman, 2014). The cucurbitacin-β, lithium, iron, and zinc found in melons can help prevent cancer and boost the immune system (Ittiyavirah et al, 2013;Raji & Orelaja, 2014;Sangamithra & Ragavi, 2020). Melons have been extensively developed and bred in Indonesia in order to generate superior cultivars and eliminate the need for imported melon cultivars.…”
Section: Introductionmentioning
confidence: 99%